Strength Properties of Untreated Coal Bottom Ash as Cement Replacement - Noraziela Syahira Baco; Shahiron Shahidan; Sharifah Salwa Mohd Zuki; Noorwirdawati Ali; Mohamad Azim Mohammad Azmi (Journal of the Civil Engineering Forum, 2020)
Coal Bottom Ash (CBA) is a mineral by-product of thermal power plants obtained from the combustion of coal. In many countries, CBA wastes are identified as hazardous materials. The utilization of CBA can help in alleviating environmental problems; thus, this research was carried out to explore the possibility of its use as cement replacement in concrete manufacturing. Presently, In Malaysia, research that concerns about the use of CBA as cement replacement is very limited. Therefore, this study was aimed to investigate the properties of CBA as cement replacement and to identify the optimum percentage of untreated CBA as cement replacement. The CBA used in this study were taken from the Tanjung Bin power plant. In this research, the amount of CBA in the concrete mixture varied from 20% to 40% to replace cement. The properties of concrete containing CBA as cement replacement was examined through slump test, sieve analysis, concrete compressive strength test and splitting tensile strength test. The compressive strength test and splitting tensile strength test were performed at 7 and 28 days of curing time. Based on this research, it can be concluded that the optimum percentage of CBA as cement replacement is 25% for a curing time of both 7 and 28 days with the concrete compression strength of 45.2 MPa and 54.6 MPa, respectively. Besides, the optimum percentage for tensile strength is also at 25% CBA for a curing period of both 7 and 28 days with the tensile strength of 2.91 MPa and 3.28 MPa, respectively.